Ethics of conduct of state servants as a qualitative component of the content of public administration - Білокур, Євгенія Ігорівна; Білокур, Є. І.; Билокур, Евгения Игоревна; Bilokur, Yevheniia I.; Даниленко, Юлія Сергіївна; Даниленко, Ю. С.; Даниленко, Юлия Сергеевна; Danylenko, Yuliia S (Riga : Izdevniecība “Baltija Publishing”, 2020)
The article is devoted to the study of the ethics of conduct of state servants as a qualitative component of the content of public administration.The concept of «ethics of conduct of state servants» is defined and the characteristic features of its content are clarified. Particular attentionis paid to the issue of legal regulation of the rules of ethical conduct of state servants. It is determined that the establishment of the rules of ethical conduct of state servants is intended to: help to prevent the commission of corruption or corruption-related offenses by state servants; to ensure an increase of the level of official discipline during service in public authorities; increase the personal responsibility of state servants for the performance of their duties.There are three groups of ethical equirements for state servants depending on the content, as: 1) organizational; 2) information; 3) personal. It was found that the General Rules of Ethical Conduct regulate the issues of ethics of state servants rather superficially, in particular without interpreting the content of certain regulations, which leads to the possibility for officials to use discretion in their official activities. It is determined that for violation of the rules of ethical conduct by state servants such types of legal consequences are applied to them as: a) bringing to legal responsibility (criminal, administrative, disciplinary); b) the onset of organizational and procedural consequences.

Стаття присвячена дослідженню етики поведінки державних службовців як якісної складової змісту державного управління. Визначено поняття «етика поведінки державних службовців» та з’ясовано характерні риси її змісту. Особлива увага приділяється питанню правового регулювання правил етичної поведінки державних службовців. Визначено, що встановлення правил етичної поведінки державних службовців має на меті: сприяти запобіганню вчиненню державними службовцями корупційних або пов’язаних з корупцією правопорушень; забезпечити підвищення рівня службової дисципліни під час служби в органах державної влади; підвищити особисту відповідальність державних службовців за виконання своїх посадових обов'язків. Залежно від змісту виділяють три групи етичних вимог до державних службовців: 1) організаційні; 2) інформаційні; 3) особистісні. Встановлено, що Загальні правила етичної поведінки регулюють питання етики державних службовців досить поверхово, зокрема без тлумачення змісту окремих нормативно-правових актів, що веде до можливості для посадових осіб використовувати розсуд у своїй службовій діяльності. Визначено, що за порушення державними службовцями правил етичної поведінки до них застосовуються такі види правових наслідків, як: а) притягнення до юридичної відповідальності (кримінальної, адміністративної, дисциплінарної); б) настання організаційно-процесуальних наслідків.
Bilokur Ye. I. Ethics of conduct of state servants as a qualitative component of the content of public administration / Ye. I. Bilokur, Yu. S. Danylenko // Public administration under modern conditions: concept, features, challenges : Collective monograph. - Riga : Izdevniecība “Baltija Publishing”, 2020. - P. 82-98.
Keywords: ethical conduct; state servant; ethical equirements for state servants; legal consequences; етична поведінка; державний службовець; етичні вимоги до державних службовців; правові наслідки; Research Subject Categories::LAW/JURISPRUDENCE::Public law